Gallbladder bed resection or hepatectomy of segments 4a and 5 for pT2 gallbladder carcinoma: analysis of Japanese registration cases by the study group for biliary surgery of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery. Issue 5 (June 2013) - Horiguchi, Akihiko; Miyakawa, Shuichi; Ishihara, Shin; Miyazaki, Masaru; Ohtsuka, Masayuki; Shimizu, Hiroaki; Sano, Keiji; Miura, Fumihiko; Ohta, Tetsuo; Kayahara, Masato; Nagino, Masato; Igami, Tsuyoshi; et al.
Abstract Purpose Hepatectomy of segments 4a and 5 (S4a+5) is the recommended treatment for pT2 gallbladder cancer. However, gallbladder bed resection is also occasionally used. Using nationwide data from the Japanese Biliary Tract Cancer Registry and a questionnaire survey, we retrospectively compared these 2 methods of treatment. Method The study involved 85 patients with pT2, pN0 gallbladder cancer (55 treated with gallbladder bed resection, and 30, with S4a+5 hepatectomy). The prognosis and mode of tumor recurrence following treatment were analyzed retrospectively, with overall survival as the endpoint. Results The 5‐year survival rate did not differ significantly between the 2 groups. Univariate analysis showed that bile duct resection and perineural tumor invasion were significant prognostic factors, but the extent of hepatectomy, location of the major intramural tumor, regional lymph node excision, and histological type were not. Multivariate analysis identified perineural tumor invasion as a significant prognostic factor. Recurrence occurred most frequently in both lobes than S4a+5 of the liver following gallbladder bed resection. Conclusion In the present study of cases of Japanese Biliary Tract Cancer Registry, it was not possible to conclude that S4a+5 hepatectomy was superior to gallbladder bed resection.